(untitled) (Studia Politica. Romanian Political Science Review, 2025)
The Left in Albania has long been synonymous with the communist successor, most notably represented by the Socialist Party of Albania (SPA). Emerging from the Cold War era, the SPA inherited not only the ideological framework, but also the political dominance that had been characteristic of communist rule. Over the past three decades, the SPA has remained one of Albania’s two dominant political parties, blending elements of socialist ideology with certain authoritarian tendencies. This legacy has contributed to an ideological and democratic void that other parties, particularly extra-parliamentary ones, have sought to fill. Among these, the Movement Together (MT) and the Hashtag Initiative (HI) have emerged as significant actors. Given the scarcity of comprehensive scholarship on Albania’s political landscape, this paper presents Albania as a case study to define and classify communist successor and other left-wing parties, drawing on frameworks applied in Central and Eastern Europe. The paper compares the platforms and political rhetoric of the SPA, MT, and HI, with a particular focus on the SPA’s conduct while in government. Moreover, the internal characteristics of these parties is examined to provide a nuanced understanding of Albania’s domestic political environment and what defines the Left in Albania.